Case report: Limb-threatening femoral vein thrombosis in a healthy carpet fitter: Carpet fitter's thrombosis. (July 2016) - Rothnie, Alex; Aga, Sarah; Vijayaragahavan, Santhosh; Nyamekye, Isaac
Objective: To report a case of femoral vein thrombosis in a carpet fitter and to highlight this as an occupational hazard. Method: Case presentation and literature review. Results: An otherwise fit 21-year-old carpet fitter with no past medical history presented with acute thrombosis of his left common femoral, superficial femoral and great saphenous veins. Attempted catheter directed thrombolysis was unsuccessful. Due to severe pain and the threat of venous gangrene he was treated by emergency surgical thrombectomy with excision of chronic venous scarring and vein-patch repair that led to resolution of his symptoms. Conclusions: Deep vein thrombosis is typically associated with factors such as increasing age and prolonged periods of immobility; however, certain 'active' occupations can increase its risk. Crouched and cramped working conditions including repetitive active movement with flexed hips and knees can predispose to increased risk of venous thromboembolism.